1996
DOI: 10.1007/bf00033123
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt induced changes in photosystem activity in Synechocystis PCC 6803: Alterations in energy distribution and stoichiometry

Abstract: Adaptive responses to excess (supraoptimal) level of cobalt supplied to the growth medium were studied in the cyanobacterium Synechocystis PCC 6803. Growth of cells in the medium containing 10 μM CoCl2 led to a large stimulation (50%) in O2-evolution and an overall increase (∼30%) in the photosynthetic electron transport rates. Analysis of variable Chl a fluorescence yield of PS II and immuno-detection of Photosystem II (PS II) reaction-center protein D1, showed a small increase (15-20%) in the number of PS II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…These results suggest that low concentrations of Co 2+ stimulate electron transport at the donor side of PSII. Our results are in agreement with those reported by Tiwari and Mohanty (1996) who observed that Synechocystis cells grown in a medium containing 10 mmol.L -1 CoCl 2 showed a large stimulation (50 %) of O 2 evolution and an overall increase (~30 %) in the rate of photosynthetic electron transport resulting from a small increase (15-20 %) in the number of PSII units in Co 2+ -grown cells.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results suggest that low concentrations of Co 2+ stimulate electron transport at the donor side of PSII. Our results are in agreement with those reported by Tiwari and Mohanty (1996) who observed that Synechocystis cells grown in a medium containing 10 mmol.L -1 CoCl 2 showed a large stimulation (50 %) of O 2 evolution and an overall increase (~30 %) in the rate of photosynthetic electron transport resulting from a small increase (15-20 %) in the number of PSII units in Co 2+ -grown cells.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with those of El-Naggar et al (1999) who found that low Co 2+ concentration increased both O 2 evolution and dark respiration in two cyanobacterial species, C. fusca and N. muscorum, whereas higher concentrations were inhibitory. Further confirmation of our results can be found in the data of Tiwari and Mohanty (1996) who reported that Synechocystis PCC 6803 cell growth in a medium containing 10 mmol.L -1 CoCl 2 exhibited a large stimulation (50 %) of O 2 evolution and an increase (~30 %) in photosynthetic electron transport. With regard to the observed inhibition as a result of the addition of higher concentrations of Co 2+ , ElSheekh and Hammouda (1992) reported that 25 and 50 mmol.L -1 Co 2+ inhibited O 2 evolution of Chlorella minutissima by 58.3 and 70.3 %, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At 750 nm the absorption of the cell suspension was adjusted to give approximately the same reading. Room temperature fluorescence emission spectra of the cells were recorded on a Perkin-Elmer LS-5 spectrofluorimeter following Tiwari and Mohanty (1996). PSII : PSI ratio analysis was done by spectrofluorimetry according to Gan et al (2014), and Amirlatifi et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…[1] However, high concentrations of Co are inhibitory for growth, chlorophyll synthesis and induce changes in photosynthetic activity. [2][3][4] Toxicity symptoms due to excess Co are chlorosis, necrosis, and root tip damage in higher plants.…”
mentioning
confidence: 99%